Living Hadith in the Digital Age: Exegetical and Aesthetic Reception of Hadith in Gita Wirjawan’s YouTube Podcast - Rahcmad Sutisna Hamijaya; Ihsan Nurmansyah; Sherli Kurnia Oktaviana (Institut Muslim Cendekia, 2026)
Digital media, particularly dialogic podcasts on YouTube, have emerged as new spaces for the dissemination and interpretation of the Prophet’s hadith. This article examined the phenomenon of living hadith in religious podcasts on the Gita Wirjawan YouTube channel, featuring dialogues with Habib Husein Ja’far Al Hadar and Muhammad Quraish Shihab. The study aimed to analyze the reception of hadith by the speakers in the form of oral discourse and audio-visual representation, focusing on hadith concerning intention as well as the teachings of Islam, īmān, and iḥsān. This research employed a descriptive-analytical approach through content analysis, using the reception theory framework developed by Saifuddin Zuhri Qudsy and Subkhana Kusuma Dewi. The findings revealedl that exegetical reception was reflected in contextual interpretations linking relate the Prophetic tradition to contemporary ethical, philosophical, and social issues. Meanwhile, aesthetic reception appears through visual elements such as natural landscapes, spatial design, bookshelves, and symbolic representations of ulama, which fostered emotional engagement while reinforcing religious authority. These findings suggested that digital podcasts function not only as a medium of da‘wah but also as a dynamic arena for the construction of hadith meaning. Academically, this study contributes to the development of living hadith studies by positioning digital media as a significant locus in the transformation of religious authority and reception in the contemporary era.